The Relationship Between Sleep Quality as A Determinant of Student Heart Rate Response in Physical Education Learning - Ahmad Tegar Fauzan; Adi S (ACTIVE: Journal of Physical Education, Sport, Health and Recreation, 2026)
Sleep quality is an important physiological factor that plays a role in the regulation of the autonomic nervous system and cardiovascular response, particularly heart rate. In students, poor sleep quality has the potential to affect heart rate response during physical activity in Physical Education, Sports, and Health (PE) learning. This study aims to analyze the relationship and influence of sleep quality on students' heart rate response in PE learning. The study uses a quantitative approach with a correlational (associative) design. It was carried out at  State Vocational School 10 Semarang with a research sample consisting of 120 students (N = 120) who were selected using random sampling techniques. Sleep quality was measured using a score scale of 1–4 (PSQI Questionnaire), while heart rate was measured in beats per minute (bpm), using the Coospo H808S device (chest strap ECG). Data analysis includes descriptive statistics, Kolmogorov-Smirnov normality test, linearity test, Pearson correlation test, and simple linear regression analysis. The results showed that there was a significant negative relationship between sleep quality and heart rate (r = -0.267; p = 0.003). Regression analysis showed that sleep quality had a significant effect on heart rate with a contribution of 7.1% (R² = 0.071). These findings indicate that better sleep quality is associated with lower heart rate and a more stable cardiovascular response during PE learning. Thus, sleep quality can be considered as one of the important factors in optimizing physical education learning and student health.